Web-based analysis on the role of Digital Media in Health Communication: the experience of VaccinarSinSardegna Website - Arghittu, Antonella; Deiana, Giovanna; Dettori, Marco; Dempsey, Emma; Masia, Maria Dolores; Plamieri, Alessandra; Spano, Antonio Lorenzo; Azara, Antonio; Castiglia, Paolo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Vaccinarsinsardegna.org website is a medical and scientific communication portal regarding vaccinations of Sardinia region. This article aims to present the structure of the portal, to demonstrate the actions carried out to provide accurate information for users and to analyse the website’s activity from its launch until the current pandemic period in terms of dissemination and visibility. Methods: Various metrics such as the number of visits to the site (sessions, number of users and average session duration), user behaviour (pages viewed, bounce rate and organic search) and the session acquisition path (direct traffic, referrals and social traffic) were recorded, extrapolated and processed with Google Analytics. Qualitative and normally distributed quantitative variables were summarised with absolute (relative) frequencies and means. The statistical differences between the two periods (before and during the anti-COVID-19 vaccination campaign) were evaluated applying the Wilkoxon runk-sum test. A two-tailed p-value less than 0.01 was considered to be statistically significant. Results: The metrics recorded using Google Analytics show that from its publication to date, the VaccinarSinSardegna.org portal has significantly increased its visibility: in fact, the number of users who have accessed the site, the number of sessions and individual web pages visited have grown exponentially. These findings are confirmed by the increasing number of visits to both versions of the regional website (Italian- and English-language) during the COVID-19 emergency and COVID-19 vaccination campaign. When the total values recorded over the period were compared, an overall increase in metrics was observed—the number of individual users, visits and individual pageviews rose in a statistically significant way. Conclusions: Based on the success on VaccinarSinSardegna and given its potential for expansion to include further collaborations with national and international scientific bodies, the authors affirm that similar initiatives should be implemented in the fight against vaccine hesistancy.